Queensland Commercial Macropod Management Program Annual Report - Queensland. Department of Environment and Heritage Protection. Environmental Services and Regulation (Brisbane : Department of Environment and Heritage Protection, 2008)
The Department of Environment and Resource Management's (the department) Commercial Macropod Management Program administers the commercial harvest of macropods in Queensland.
Title from PDF cover page (viewed on August 16, 2015).
Reporting year runs from 1 January to 31 December ...
Keywords: Queensland. -- Department of Environment and Heritage Protection -- Periodicals; Kangaroos -- Control -- Queensland -- Periodicals; Kangaroos -- Queensland -- Management -- Periodicals